Uso das técnicas de orçamento de capital nas empresas com ações negociadas na BOVESPA no segmento Novo Mercado - Paula, Jane Keilly de (2009)
The capital budgeting decisions are very important for the future of a company, because it is through the investment in new machines, equipments, obligatory projects and other capital expenses, that the company assures survival and growth. As those types of investments usually commit great volumes of resources for a long period of time, becomes also extremely important the analysis process used in the evaluation, comparison and selection of investment projects. In that context, the main objective of this study is to investigate the use of capital budgeting techniques in the companies with stocks negociated in the São Paulo Stock Exchange (Bovespa) in the New Market segment. The used methodology was the descriptive research and the data were collected through a questionnaire with open questions sent by e-mail and, after the completion, returned by the same way. It has been made a comparison of the obtained results in this work with two researches accomplished in the decade of 80, whose differences of method and universe were detailed. The results show that the companies are developing along the time in the application of techniques and tools of investment analysis. It was verified that the Net Present Value (NPV) it is the main technique more used (56,3%) and the criterion of the capital recovery time (Payback) it is the second technique more used by the companies (37,5%). Therefore, the conclusion that the companies are following the theoretical recommendation that it considers NPV as the most complete method for the taken of investment decision